Satisfaction Work of Teachers and Education Personnel at Ma'arif Elementary School - Karim Ar Rasyid, M. Abdul; Wibowo, Gilang Bakti Peran; Megawati, Megawati; Hafiidhy, Luthfi Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2025)
Satisfaction Work is one of factor important that influences performance and well-being power educators at school. Study This aiming For to obtain better understanding​ deep about experience work , influencing factors​ satisfaction work , and its influence to quality teaching and service education in school said . With use approach qualitative , research This will focuses on the experiences , views and perceptions of teachers as well power education about factors that influence satisfaction Work they are at Ma'arif Elementary School, West Bandar Jaya . Research This use approach qualitative with design studies case , Data collection using method interviews , observations and documentation . Data analysis using data reduction , data presentation , drawing conclusions. Research results show that factors main influencing factors satisfaction work of teachers and staff education in schools This includes : (1) environment adequate physical and facilities​ adequate , although there is a number of aspects that need to be considered improvements , such as teacher's room and facilities sports ; (2) positive interpersonal relationships between fellow colleague work and head school , create atmosphere comfortable and supportive work ; ( 3 ) recognition and rewards given Already Enough Good ,teachers and staff education accept in form material or non- material , a little the amount has give impact positive to motivation Work they . Awards this , although Already there is , still Can fixed in matter justice and consistency For more increase performance and satisfaction Work power educator . some teachers suggest that awards more even and fair . In addition , (4) balance between work and life personal become necessary factors​ be noted , because some teachers feel burden Work sometimes bother time personal they.